Biological activity of improved color maize (Zea mays) grown in southern Sonora - Cadena Cadena, Francisco (2024)
Introduction. In Mexico, 85 % of the crops are white maize, 10 % white yellow and 5 % other colors. Biochemical studies of pigmented native maize have been carried out, but there is little information on colour-improved maize. Objective. To evaluate the phytochemical content and antimicrobial capacity of two pigmented maize hybrids grown at the Tecnológico Nacional de México-Valle del Yaqui. Materials and methods. Extraction of biocompounds from a portion of the maize grains grown in southern Sonora, Mexico, during the summer-winter 2020 cycle was performed on red and purple maize hybrids. A thirty-part solution of ethanol, acetic acid and water was used. Proximal composition, anthocyanin, polyphenol and flavonoid content were determined by standardized methods. Antioxidant capacity was determined by ABTS (2,2’-azino-bis-(3-ethylbenzothiazoline-6- sulphonic acid)) and DPPH (2,2-diphenyl-1-picrylhydrazyl) methodologies. In addition, antimicrobial capacity and minimum inhibitory concentration were determined. Results. Purple maize showed higher content of anthocyanins (340.98±5.21 mg/100 g) and polyphenols (173.68±24.23 mg gallic acid/100 g) compared to red maize. Flavonoids are more abundant in purple maize (575.10±27.88 mg quercetin/100 g). Both maize hybrids exhibited more than 50 % antioxidant capacity against ABTS and DPPH radicals. Regarding antimicrobial activity, higher inhibition was observed for Escherichia coli and Salmonella (18 % and 47 %), and lower for Staphylococcus aureus and Shigella (19 % and 34 %) compared to gentamicin. Conclusion. Purple maize showed higher content of anthocyanins, polyphenols and flavonoids. Both hybrids had an antioxidant capacity higher than 50 %. Antimicrobial activity was higher against E. coli and Salmonella, than against S. aureus and Shigella.